Associations between elevated depressive symptoms and substance use, prescription opioid misuse, overdose history, pain, and general health among community pharmacy patients prescribed opioids. Issue 1 (1st December 2022) - Brown, Jennifer L.; Cochran, Gerald; Bryan, M. Aryana; Charron, Elizabeth; Winhusen, T. John
Abstract: Background: Individuals with pain prescribed opioids experience high rates of comorbid depression. The aim of this study was to characterize pain, substance use, and health status as a function of depressive symptom level in individuals filling an opioid prescription at a community pharmacy. Methods: Participants ( N = 1268) filling an opioid prescription enrolled in a study validating a prescription drug monitoring metric completed an online survey assessing sociodemographics, depressive symptoms, substance use, prescription opioid misuse, overdose history, general health, and pain severity and interference. Results: Approximately one-fifth (19.3%) had a positive depression screen result. In covariate-adjusted logistic regression analyses, individuals with a positive depression screen result were more likely to have moderate/high substance use risk scores for prescription opioids (adjusted odds ratio [AOR] = 2.06; 95% confidence interval [CI], 1.51–2.79); street opioids (AOR = 7.18; 95% CI, 2.57–20.01); cannabis (AOR = 2.00; 95% CI, 1.34–3.00); cocaine (AOR = 3.46; 95% CI, 1.46–8.22); tobacco (AOR = 1.59; 95% CI, 1.18–2.15); methamphetamine (AOR = 7.59; 95% CI, 2.58–22.35); prescription stimulants (AOR = 2.95; 95% CI, 1.59–5.49); and sedatives (AOR = 3.41; 95% CI, 2.43–4.79). Individuals with a positive depression screen were more likely to misuse prescription opioids (AOR = 3.46; 95% CI, 2.33–5.15), experience a prior overdose (AOR = 2.69; 95% CI, 1.76–4.11), report poorer general health (AOR = 0.25, 95% CI, 0.18–0.35), and report moderate/severe pain severity (AOR = 4.36, 95% CI, 2.80–6.77) and interference (AOR = 6.47, 95% CI, 4.08–10.26). Conclusions: Individuals prescribed opioids with heightened depression were more likely to report other substance use, prescription opioid misuse, prior overdose, greater pain, and poorer health.